Clinical outcomes after vascular reconstruction using synthetic grafts for limb salvage in patients with lower extremity sarcoma: a single-center retrospective experience - Zheng, Chuanxi; Xu, Gang; Li, Wei; Weng, Xin; Yang, Hongwei; Wang, Zuhui; Zhang, Shiquan (Frontiers in Oncology, 2023)
Introduction Limb-salvage surgery has become the mainstream approaches for the treatment of sarcoma in the lower extremity. In cases where the sarcoma infiltrates the primary vessel, concurrent resection of the vessels and vascular reconstruction are required to ensure sufficient resection and preservation of limb function. The objective of this study is to assess the clinical outcomes of patients who underwent vascular reconstruction utilizing synthetic grafts for limb salvage, specifically in terms of postoperative complications and limb functional status. Methods Between September 2016 and October 2021, 15 consecutive patients who underwent 15 arterial and 3 venous reconstruction procedures were included in this retrospective study. Incidence of postoperative morbidity, graft patency, rate of limb salvage, and overall survival of patients were analyzed. Results The median follow-up was 12.5 months (range, 4.5-72.0). Graft thrombosis occurred in 5 patients (33.3%) and graft occlusion occurred in 3 patients (20.0%). The median overall survival was 28.0 months with the estimated 2-year and 5-year overall survival of 57.8% and 43.4% respectively. The 1-year and 2-year estimated patency rates of arterial reconstructions were 82.3% and 62.1%, respectively. None of the included patients with limb amputation were observed as a consequence of severe vascular complications, while two patients underwent amputation due to the repeat recurrence, resulting in a limb salvage rate of 86.7%. Conclusion Our results show that the combination of vascular reconstruction and oncologic resection is a feasible option for preserving limbs in cases of musculoskeletal sarcoma with vessel involvement in the lower extremity. When vascular reconstruction surgery is performed, synthetic substitutes can be effectively used with low perioperative morbidity and an acceptable rate of limb salvage.